STUDY OF A CENTRIFUGAL PUMP, ASYNCHRONOUS MOTOR AND INVERTER, USING HARDWARE IN THE LOOP SIMULATION CONCEPT - HOUNGUE, Cessac Franck Clair; HOUNGAN, KOKOU THÉOPHILE; AGBOKPANZO, RICHARD GILLES; SANYA, MAX FREJUS O.; ADJOVI, EDMOND CODJO (My University, 2014)
This work is about a low coast application of Hardware In the Loop simulation (HILS) concept to the study of a three-phase inverter, asynchronous motor and centrifugal pump. It presents the realization of the rectangular control using a micro controller (ATMEGA 168). The signals generated by the micro controller have been used to program the parallel port of a computer. By reading the recorded bits of the parallel port in LabVIEW software, the signals from the micro controller have been restored and made available to the simulation model of the three-phase inverter, asynchronous motor and centrifugal pump, made in advance in LabVIEW. These models realized in the computer are then controlled by external signals coming from the micro controller. The challenge was to be able to transfer signals from the micro controller to the model lodged on the computer and perform a simulation like in classical case, where all the system under study is simulated. We compare the results of our simulation with those of classical simulation. We notice that both results match.
Keywords: ATMEGA168; Hardware In the Loop Simulation; voltage inverter; asynchronous motor; centrifugal pump.